Promosi untuk Menarik Minat Pemustaka di Politeknik Negeri Banjarmasin - Fitri Ani Dahrani; Rustaniah Rustaniah; Novi Shintia (P3M Politeknik Negeri Banjarmasin, 2022)
The library is a means provided to obtain information, but awareness of the importance of reading is still low, which causes a low number of visits to the library. To overcome this problem, promotion is needed. The purpose of this study is to find out promotions to attract the interest of users in the Banjarmasin State Polytechnic Library. This research is a type of field research using a descriptive qualitative research approach. With the methods of data collection, observation, interviews, and documentation. The subjects in this study were the head of the library of the Banjarmasin State Polytechnic and 2 librarians. The object of this study was a promotion to attract the interest of users at the Banjarmasin State Polytechnic library. Data analysis techniques used are data reduction, data presentation, data analysis, and conclusion.The results showed that the strategy of the Banjarmasin State Polytechnic library in carrying out promotions to attract users' interest was twofold, namely: the first: formulation which included problem identification, target setting, work plan preparation, and budget formulation. Second: implementation (implementation). The forms of promotion carried out are individual contacts, advertisements, lectures, and renovations.